2018
DOI: 10.1097/bpb.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term high-load exercise on the anatomy of the hip joints: a preliminary report

Abstract: The aim of this study was to assess the impact of different sports on hip joint anatomic parameters in athletes. This was a cross-sectional study of eight male trampolinists, eight male weightlifters, and eight male volunteers enrolled in July 2014. Hip joint anatomic parameters were measured from plain radiographs taken at the level of the lesser trochanter center. Data were compared between groups using the χ-test or one-way analysis of variance with the Bonferroni post-hoc test. There were no significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…The reason for this hypotrophic appearance of the femoral neck may be that in C2 femurs, the load only partially transfers through the femoral neck due to the absence of a false acetabulum. It has been reported that load transfers during the developing period are associated with a longer femoral neck and higher NSA [14,15]. We also found that the greater trochanter, but not the femoral head, migrated more superiorly in C2 femurs.…”
Section: Discussionsupporting
confidence: 66%
“…The reason for this hypotrophic appearance of the femoral neck may be that in C2 femurs, the load only partially transfers through the femoral neck due to the absence of a false acetabulum. It has been reported that load transfers during the developing period are associated with a longer femoral neck and higher NSA [14,15]. We also found that the greater trochanter, but not the femoral head, migrated more superiorly in C2 femurs.…”
Section: Discussionsupporting
confidence: 66%
“…To act and move accurately, the nervous system must be able to read the shape and size of one's own body and its orientation in space. Long-term intensive training also affects skeletal anatomical parameters, especially with younger athletes (Song et al, 2018;Steinberg et al, 2017;Yang et al, 2014). Highly skilled female karate athletes with advanced technical efficiency, high basic, and specific motor efficiency were identified to have a wider wrist and fist diameter (Jukić et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…More than two-thirds of these participants had evidence of asymptomatic hip pathological lesions on MRI. In a study, 35 the impact of long-term high-intensity training in different sports on hip joint anatomic parameters in athletes (trampolinists and weightlifters) has been determined.…”
Section: Discussionmentioning
confidence: 99%